Newcastle disease virus (NDV) modulates pro/antioxidant status in different brain regions of chicken - Subbaiah, Kadiam C. Venkata; Wudayagiri, Rajendra; Valluru, Lokanatha (Free Radicals and Antioxidants)
Background: Newcastle disease (ND) is highly contagious disease caused by Newcastle disease virus (NDV) causes mass mortalities in poultry and triggers poultry economy. Methods: NDV induced oxidative stress representing marker enzymes and lipid peroxidation levels were evaluated in tissues of control and virus infected animals by using standard protocols and methods. Results: Lipid peroxidation levels were significantly increased in cerebrum and cerebellum of NDV infected chickens on 10 (dpi) as compared to controls. The activities of superoxide dismutase, catalase and glutathione metabolism representing enzymes were significantly decreased in cerebrum and cere- bellum. Extensive histopathological malformations were observed in cerebrum and cerebellum. Conclusion: The results of the present study, thus demonstrated that region specific alterations in the antioxidant defense mechanism due to NDV infection suggesting its critical role in cellular injury prominently in cerebrum and cerebellum and moderately in optic lobes of brain. The findings could help to advance the therapeutic armamentarium for control of Newcastle disease in poultry.
Keywords: Newcastle disease virus; Brain regions; Oxidative stress; Antioxidant metabolism; Chicken